COMPANY SIZE, MANAGERIAL, INTITUTIONAL OWNERSHIP AND ENVIRONMENTAL PERFORMANCE ON CORPORATE SOCIAL RESPONSIBILITY DISCLOSURES - Liana Mariam Ulfa; Siti Nur Azizah; Ira Hapsari (Review of Applied Accounting Research (RAAR), 2021)
The purpose of this study is to empirically prove the effect of firm size, board size, institutional ownership, and managerial ownership on CSR disclosure. The sample in this study were mining companies listed on the Indonesia Stock Exchange in 2015-2019 using the purposive sampling method. Based on the criteria, there were 67 samples of research data. The data analysis technique used in this research is descriptive statistical analysis, classical assumption test, multiple linear regression analysis, and hypothesis testing. This study shows that, partially, company size, institutional ownership, and managerial ownership do not affect CSR disclosure. Meanwhile, the environmental performance has a positive effect on CSR disclosure